Use of technologically and topologically related surfaces (TTRS) geometrical theory for mechatronic design ontology. Issue 5 (29th July 2017) - Plateaux, Régis; Penas, Olivia; Barbedienne, Romain; Hehenberger, Peter; Choley, Jean-Yves; Warniez, Aude
ABSTRACT: This paper presents the MBSE challenges related to the conceptual design of mechatronic systems and especially the need to ensure geometrical knowledge consistency. To tackle this issue, we propose to define an ontology based on the TTRS (Technologically and Topologically Related Surfaces) geometrical modeling. We implement it in the Protégé environment and validate it through the modeling process of an Electric Power Train, including many additional geometrical issues related to mechatronic system design, such as physical integration and the related compactness metric and the thermal modeling for multi-physical couplings. Geometrical knowledge consistency has been ensured through a model transformation between SysML and FreeCAD, using Python. GRAPHICAL ABSTRACT: